ANALYSIS OF DENICKELIFICATION PHENOMENON ON HEAT EXCHANGER TUBE - Amin Suhadi; Eka Febriyanti; Laili Novita Sari (BRIN, 2018)
DeNickelification is common phenomenon which occurs for alloy metal containing sufficient amounts of Nickel when it is exposed at high temperature in long time periode. One of component which is made of alloy metal containing Nickel is heat exchangers tube. Heat exchanger is a part of processing unit that use for transfering heat from hot fluid to colder fluid through the combined mechanisms of conduction and convection. When the heat exchanger leaks, all of the processing system could be affected. In this research a leakage heat exchanger tube is investigated by failure analysis methods to find the root cause of failure. Several tests and examinations such as fractography, metallography examinations, SEM and EDS, hardnes as well as chemical compositions test are carried out to this tube to obtain detailed information for further analysis.Result of this reseach shows that some Cu residue, Ni, aggressive/corrosive ion such as Cl- and S2- at the leak area of heat exchanger tube is found. These evidences indicated that denickelification was occurred on inner surface of heat exchanger tube caused by potential difference between Ni2+ion and Cu2+ ion to form a galvanic cell. Furthermore, since the tube is flown by fluid material which contains aggressive / corrosive ions such as Cl- ion and S2- then pitting corrosion on inner surface of tube is formed. This mechanism had been taken place continuously during operation of heat exchanger and pitting corrosion keep growing until the tube leaks.